Real-Time Animation with Adobe Character Animator Animate Characters in Real Time with Webcam, Microphone, and Custom Actions. - Troftgruben, Chad (Packt Publishing, Limited, 2022)
Build real-time animations without expensive equipment using this quick how-to guide printed in full-color Key Features Get the hang of enhancing and polishing character rigs Create quick and effective animations for business or entertainment without having to delve into all the intricacies of the craft Create triggers to customize your animated experience Book Description Adobe Character Animator is a power app for non-animators that provides easy rigging and easy-to- understand tools that enable you to create entertainment or business videos in no time. This guide to Character Animator gives you a comprehensive overview of the app, helping you learn the entire process--from importing a character designed in Adobe Photoshop to animating a sequence. Complete with background art, multiple character rigs and Character Animator project files, this book will show you how to animate a scene in Character Animator from start to finish. Starting with a character PSD from another artist, you'll organize and condense the file to prepare it for rigging and animation. From there, you'll systematically rig the character while exploring advanced behaviors and triggers to animate a complex scene that takes advantage of the app's best features. By the end of this book, you'll be able to create appealing animations in Character Animator for any purpose. What you will learn Assemble rigs in Photoshop for Character Animator Add tags, handles, draggable limbs, swap sets, and physics effects Use a webcam and microphone for lip-syncing, head turns, and other real-time actions Work with multiple characters, scene layers, and audio files Add loopable motions such as walk cycles Record a short animation for export Who this book is for If you are a beginner in animation and looking to get up and running quickly by creating your own animated scenes, this is the book for you. With just basic computer knowledge and a webcam and microphone connected, you'll be able to follow along effectively. Although not a prerequisite, knowing the principles of animation or having any history with other animation software will be helpful.